1974
DOI: 10.1177/001316447403400307
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Effect of the Number of Scale Intervals on Principal Components Factor Analysis

Abstract: EDUCATIONAL AND PSYCHOLOGICAL MEASUREMENT 1974, 34, 537-545. The effect of the number of scale intervals of a continuous variable on the results of principal components factor analysis was investigated. Analyses were performed for seven different numbers of scale intervals. The general effect was a decrease in the size of the eigenvalues, communalities, and factor loadings as the number of scale divisions was reduced. The magnitude of the effect was, however, not large and the pattern of the rotated facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 7 publications
1
14
0
1
Order By: Relevance
“…Of these, 86 percent used ordinal multi-category answer formats. Matell and Jacoby 1971;Jacoby and Matell 1971;Remington et al 1979;Preston and Colman 2000) or valid than multi-category ordinal answer formats Jacoby and Matell 1971;Preston and Colman 2000), and do not lead to different findings with regard to the structural equivalence of constructs (Martin et al 1974;Percy 1976). …”
Section: Jmmentioning
confidence: 95%
“…Of these, 86 percent used ordinal multi-category answer formats. Matell and Jacoby 1971;Jacoby and Matell 1971;Remington et al 1979;Preston and Colman 2000) or valid than multi-category ordinal answer formats Jacoby and Matell 1971;Preston and Colman 2000), and do not lead to different findings with regard to the structural equivalence of constructs (Martin et al 1974;Percy 1976). …”
Section: Jmmentioning
confidence: 95%
“…While Martin et al (1974) and Percy (1976) re-categorized empirical data to achieve this, Green and Rao (1970) used artificial data and were thus able to compare the results to the true specifications. Martin et al (1974) compare factor analysis results from ordinal multi-category and binary data (both collapsed from responses collected on a metric format) concluding that results do not differ between two and nine answer categories. The same approach was taken by Percy (1976) who constructed binary data from a multi-category data set resulting from a 5-point Likert scale.…”
Section: Interpretabilitymentioning
confidence: 99%
“…Further, the answer format in this study (a 4-point scale) differed from that in pupil studies (a 5-point scale) to force a decision from the subjects. However, it was shown that a reduction of scale divisions may also diminish factor loadings and communalities (Martin et al 1974).…”
Section: The Two-dimensional Model Of Ecological Valuesmentioning
confidence: 99%